2019
DOI: 10.1371/journal.pone.0211495
|View full text |Cite
|
Sign up to set email alerts
|

Industry payments to physician journal editors

Abstract: BackgroundOpen Payments is a United States federal program mandating reporting of medical industry payments to physicians, increasing transparency of physician conflicts of interest (COI). Study objectives were to assess industry payments to physician-editors, and to compare their financial COI rate to all physicians within the specialty.Methods and findingsWe performed a retrospective analysis of prospectively collected data, reviewing Open Payments from August 1, 2013 to December 31, 2016. We reviewed genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In 2015, 46% (320/703) of editors from 60 influential USA journals in six medical specialties received general payments from industry, of whom 48% (152/320) received payments of more than US$5000—the threshold considered significant by the National Institutes of Health 10. In 2013−2016, 42% (141/333) of USA-based physician-editors working in 35 journals with the highest number of citations in 2015 in seven medical specialties received industry payments within any given year 11. Median general payments to editors were mostly higher compared with all physicians within the same specialty 11.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, 46% (320/703) of editors from 60 influential USA journals in six medical specialties received general payments from industry, of whom 48% (152/320) received payments of more than US$5000—the threshold considered significant by the National Institutes of Health 10. In 2013−2016, 42% (141/333) of USA-based physician-editors working in 35 journals with the highest number of citations in 2015 in seven medical specialties received industry payments within any given year 11. Median general payments to editors were mostly higher compared with all physicians within the same specialty 11.…”
Section: Discussionmentioning
confidence: 99%
“…Such behavior represents a tension between the reviewers wishing to prevent the publication of flawed research, and the publishers who wish to publish highly topical studies on things such as the NFL. Recent research has also demonstrated that widespread industry funding for published medical research often goes undeclared, and that such conflicts of interest are not appropriately addressed by peer review [44,45].…”
Section: Topicmentioning
confidence: 99%
“…It is often mentioned in popular science articles that the research outputs of researchers in South America, Asia, and Africa is disappointingly low. Sub-Saharan Africa is often singled out and chastised for having "13.5% of the global population but less than 1% of global research output" 44 . This oft-quoted factoid is based on data from a World Bank/Elsevier report from 2012 which relies on data exclusively from Scopus 45 .…”
Section: Topic 9: Are Web Of Science and Scopus Global Platforms Of Kmentioning
confidence: 99%
See 1 more Smart Citation
“…"desperate" to stop their publication. Recent research has also demonstrated that widespread industry funding for published medical research often goes undeclared and that such conflicts of interest are not appropriately addressed by peer review (Wong, Avalos, and Callaham 2019;Weiss and Davis 2019).…”
Section: Figurementioning
confidence: 99%